MODEL PEMBINAAN REMAJA DI ERA PANDEMIK DENGAN PA BGA: Indonesia - Hasahatan Hutahaean; Berton Bostang Hamonangan Silaban (Jurnal PKM Setiadharma, 2020)
This Community Service is aimed at the youth category for Bible study activities. In the pandemic era since the end of February 2020, various activities in the realm of stewardship must also participate in government recommendations as part of breaking the chain of coronavirus transmission. Therefore, online media is used to create youth coaching by selecting the zoom application in its implementation. The coaching method starts with planning, implementing, finding partners for cooperation, and implementing activities. Of course, it ends with an evaluation of the activities. The Bible study model used this time is reading the Bible from the narrative genre. The community service team found great passion in youth while participating in Bible study coaching using the Bible Digging Method (BGA). The method was felt to be simple, practical, and able to bring Bible readers to find text messages. The implementation of community service must be carried out and pursued even in a pandemic situation. Youth spirituality is very important to build their future. The Word of God is a powerful material for developing youth spirituality, for a fresh, strong, and alert spiritual life